2010
DOI: 10.1021/ie101801c
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Synthesis of a High Purity Bioethanol Distillation Column Using Ionic Liquids

Abstract: In this work, we address the optimal economical synthesis of an extractive distillation column for bioethanol purification, using ionic liquids as a type of solvent that can be designed to feature sustainable characteristics, such as low toxicity and low volatility, among other desirable properties. For the optimal synthesis of the separation scheme, we propose a mixed-integer nonlinear programming (MINLP) formulation, merged with disjunctive programming tools, to take care of modeling logical decisions [Yeoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…For the single EDC, the simultaneous optimization of IL entrainers and the extractive distillation process has been addressed recently by some researchers. To this end, there are two optimization approaches: (1) the molecular structures of ILs were first designed by means of CAMD, and then, the separation scheme was optimized to determine the optimal design and operating variables using the multistage equilibrium model . (2) Both problems were solved in a simultaneous manner in which the MESH equations are incorporated into an MINLP formulation to simulate the EDC, as suggested by Valencia‐Marquez et al…”
Section: Process Simulation and Optimizationmentioning
confidence: 99%
“…For the single EDC, the simultaneous optimization of IL entrainers and the extractive distillation process has been addressed recently by some researchers. To this end, there are two optimization approaches: (1) the molecular structures of ILs were first designed by means of CAMD, and then, the separation scheme was optimized to determine the optimal design and operating variables using the multistage equilibrium model . (2) Both problems were solved in a simultaneous manner in which the MESH equations are incorporated into an MINLP formulation to simulate the EDC, as suggested by Valencia‐Marquez et al…”
Section: Process Simulation and Optimizationmentioning
confidence: 99%
“…Multiple desired and undesired side reactions in the biorenewable conversion process will lead to very complex and even azeotropic multicomponent mixtures, together with insolubility of biorenewables in conventional solvents require novel organic solvents for the pretreatment, molecular transformations and separation. As an example, ionic liquids are extensively used for biorenewable pretreatments65 and separation units 66, 67. As known, costs of separation units which are often energy extensive operations will be the dominating factor in the overall cost of a biorenewable conversion process.…”
Section: Optimal Synthesis For Biorenewable Conversion Processmentioning
confidence: 99%
“…Several authors have reported that such solvents promote significant changes on the vapor-liquid equilibrium (VLE) properties of the ethanol-water system, improving the ethanol dehydration process with larger separation factors at low ethanol concentrations [11][12][13]. Some design methodologies have been suggested for extractive distillation columns for ethanol dehydration using ILs as entrainers, such as those proposed by Chavez-Islas et al [14], Roughton et al [15], Ramírez-Corona et al [16] and Zhu et al [17] Some experimental works have also evaluated the feasibility of using such solvents at a pilot plant scale that show promising perspectives for their application [18][19][20]. ILs have also been analyzed for the separation of other mixtures, such as methyl acetatemethanol [21] and those that need desulfurization tasks [22].…”
Section: Introductionmentioning
confidence: 99%